Pediatric Colorectal Carcinoma is Associated With Excellent Outcome in the Context of Cancer Predisposition Syndromes - Weber, Marie; Schneider, Dominik T.; Offenmüller, Sonja; Kaatsch, Peter; Einsiedel, Hagen Graf; Benesch, Martin; Claviez, Alexander; Ebinger, Martin; Kramm, Christof; Kratz, Christian; Lawlor, Jennifer; Leuschner, Ivo; et al. (Pediatric Blood & Cancer, 2016)
Colorectal carcinoma (CRC) is the second most common adult cancer in Germany, however, it is extremely rare in children and adolescents. In these patients, previous literature describes aggressive behavior and diagnosis at advanced stage.Thirty-one patients with CRC age <= 18 years and treated between 1990 and 2012 have been identified through the structures and registries of the German Society for Pediatric Oncology and Hematology.The age range was 9-18 years (median 13.5 years); the median follow-up time was 43.9 months (range 1-124 months). Twenty-six patients (84%) were tested for a genetic tumor syndrome (GTS); of these, 11 patients (35% of all patients) tested positive (eight cases of Lynch syndrome, one patient with familial adenomatous polyposis, two patients with constitutional mismatch repair deficiency). An unfavorable histology was reported in 55% of the records (n = 17), a poor differentiation (grade III) in 68% of carcinoma (n = 21). Overall survival (OS) and event-free survival at 5 years was 52.0% and 65.6%, respectively. Five-year survival according to stage was 100% in stage II (n = 2), 100% in stage III (n = 13), and 12.9% in stage IV (n = 15; P < 0.001). Five-year OS in patients with and without a defined GTS was 100% and 36.5% (P = 0.019), respectively.Children and adolescents with CRC are frequently diagnosed in advanced stages and have an unfavorable prognosis. In this study, a high percentage of pediatric CRC patients presented with a tumor predisposition syndrome and showed an especially favorable OS.
EVALuna2:15175